2013
DOI: 10.1016/j.pnpbp.2013.04.019
|View full text |Cite
|
Sign up to set email alerts
|

White matter deficits in first episode schizophrenia: An activation likelihood estimation meta-analysis

Abstract: The current findings provide evidence confirming the lack of connection in the fronto-limbic circuitry at the early stages of the schizophrenia. Because the coordinates reported in the primary literature were highly variable, future investigations with large samples would be required to support the identified white matter changes in FES.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
82
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 92 publications
11
82
1
5
Order By: Relevance
“…Recent studies have shown that myelination is essential for social experience-based cognition and motor skill learning [31][32][33] [34][35][36] , abnormalities of the myelin sheath may contribute to defects of neuronal function. Increasing evidence has shown that the impairment of white matter integrity is prominent in schizophrenic brains [10,11,14,15] and further underscores the importance of the myelin sheath in schizophrenia, pointing to myelin repair as a potential therapeutic strategy for schizophrenia. In support of this notion, quetiapine, an atypical anti-schizophrenic drug, has been found to be potent in promoting the differentiation of OLs in vitro and enhancing remyelination in mouse models of demyelination [17][18][19][20] .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that myelination is essential for social experience-based cognition and motor skill learning [31][32][33] [34][35][36] , abnormalities of the myelin sheath may contribute to defects of neuronal function. Increasing evidence has shown that the impairment of white matter integrity is prominent in schizophrenic brains [10,11,14,15] and further underscores the importance of the myelin sheath in schizophrenia, pointing to myelin repair as a potential therapeutic strategy for schizophrenia. In support of this notion, quetiapine, an atypical anti-schizophrenic drug, has been found to be potent in promoting the differentiation of OLs in vitro and enhancing remyelination in mouse models of demyelination [17][18][19][20] .…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, properly myelinated nerve fibers allow precise and accurate information to fl ow within and between neuronal circuits [3,8,9] . A number of imaging studies have shown that the white matter volume of schizophrenic brains is lower than in healthy controls, suggesting that myelin sheath damage or demyelination is involved in the schizophrenic brain [10][11][12][13][14][15] . In line with this hypothesis, microarray analyses have shown that genes down-regulated in schizophrenic brains are related to OL development and myelination, arguing that myelin repair may be an unmet need that has been overlooked in therapies for schizophrenia [16] .…”
Section: Introductionmentioning
confidence: 99%
“…65 Our finding of lower FA within the IFOF among individuals higher in psychometric schizotypy is consistent with prior work implicating dysfunction of this tract in the neurobiology of SZ. For example, Yao et al 66 reported white matter deficits in first-episode SZ in the left IFOF using an activation likelihood estimation meta-analysis involving 8 studies that included 271 first-episode patients and 297 healthy controls. Moreover, the observation of lower FA within the left IFOF among first-episode neuroleptic-naive patients compared with healthy volunteers suggests these effects are not an artifact of antipsychotic medication exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, long-range white matter projections into the higher-order cortical regions of the frontal lobes may be associated with positive symptoms. 6,12 At a cellular level, dysfunctional glutamatergic synapses involved in synaptic plasticity may cause the delayed corollary discharges. 13 Several neurotransmitters, such as acetylcholine, serotonin and dopamine, modulate the synapses at the glutamate (N-methyl-d-aspartate [NMDA]) receptors.…”
Section: Introductionmentioning
confidence: 99%